The role of diplomatic means in the settlement of international disputes - Noureldin, ElMoatazbellah Mohamed Mohamed (Journal of Economic, Administrative and Legal Sciences, 2024)
Relations between states are not always stable and calm, and the conflict of interests of these states often leads to conflict between them, and the wisdom dictates in such a case that these states should seek to settle the conflict amicably, and not to resort to violent means unless necessary. Since the end of the last century, the efforts of peace-loving politicians have been directed towards replacing peaceful means with force in the settlement of international disputes.for this purpose, major conferences were held, such as The Hague Conference in 1899 and 1907, in which a set of provisions were decided to settle international disputes by peaceful means. this research deals with the role of diplomatic means in settling international disputes, identifying diplomatic means for settling international disputes, and identifying the nature of decisions resulting from peaceful means used in settling international disputes. It is derived from:1-the settlement of international disputes is carried out on the basis of respect for the principle of sovereign equality between states, and in accordance with the principle of free choice of means of settlement, taking into account the non-arbitrariness of the state in using its right to choose the means of settlement.2-the determination of the means of settlement is up to the will of the parties to the conflict, who have the freedom to determine it either by agreement between them before any dispute arises or by agreement after the dispute arises.This study has come up with the most important recommendations, including studying the causes of conflicts, developing appropriate remedies for them before they escalate and reach the point of armed confrontation, urging them to be resolved by peaceful means, reviewing international conventions and treaties, including the Charter of the United Nations, activating the negotiation mechanism to resolve international conflicts.
Keywords: diplomatic means; international conflicts